EFFECTIVE PRODUCTION MANAGEMENT AND FINANCIAL CONTROL IN ENTERPRISES: IMPLEMENTATION OF FINANCIAL CONTROL MECHANISMS FOR EFFECTIVE MANAGEMENT OF PRODUCTION PROCESSES (Conferencea, 2024)
Production management and financial control play crucial roles in the success and sustainability of enterprises, directly influencing productivity, efficiency, and profitability. This article explores the intersection of production management and financial control, emphasizing the importance of financial control mechanisms for enhancing production efficiency. It examines various financial control mechanisms, such as budgeting, cost accounting, and performance evaluation, and discusses their implementation within production processes. By using case studies and practical examples, the article demonstrates how enterprises can achieve operational excellence and financial stability through well-coordinated production management and robust financial controls.